1996
DOI: 10.1128/mcb.16.7.3685
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Colony-Stimulating Factor 1 Receptor Signaling by the SH2 Domain-Containing Tyrosine Phosphatase SHPTP1

Abstract: SHPTP1 (PTP1C, HCP, SHP)is an SH2 domain-containing tyrosine phosphatase expressed predominantly in hematopoietic cells. A frameshift mutation in the SHPTP1 gene causes the motheaten (me/me) mouse. These mice are essentially SHPTP1 null and display multiple hematopoietic abnormalities, most prominently hyperproliferation and inappropriate activation of granulocytes and macrophages. The me/me phenotype suggests that SHPTP1 negatively regulates macrophage proliferative pathways. Using primary bone marrowderived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 54 publications
6
141
1
Order By: Relevance
“…The immobilized SHP-1 fusion proteins were ligated to synthetic peptides in the presence of 2% thiophenol. 2 The purity of the semisynthetic proteins was determined by 10% SDS-PAGE stained with Coomassie Blue and by MALDI mass spectrometry (Ͼ90%). The yield was 2-10 mg of protein/liter in E. coli cell culture as revealed by Bradford assay (24).…”
Section: Methodsmentioning
confidence: 99%
“…The immobilized SHP-1 fusion proteins were ligated to synthetic peptides in the presence of 2% thiophenol. 2 The purity of the semisynthetic proteins was determined by 10% SDS-PAGE stained with Coomassie Blue and by MALDI mass spectrometry (Ͼ90%). The yield was 2-10 mg of protein/liter in E. coli cell culture as revealed by Bradford assay (24).…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent study [11], we demonstrated that this pV-mediated protection against leishmaniasis was in part due to an increased production of nitric oxide and pro-inflammatory molecules (such as IL-6, IL-1b, MCP-1/CCL2 and MIP-2/CXCL1), accompanied by increased leukocyte recruitment. Furthermore, we showed that the PTP Src homology 2 domain phosphotyrosine phosphatase 1 (SHP-1), recognized as a negative regulator of numerous phosphotyrosine-dependent signaling pathways in hematopoietic cells [12][13][14][15][16][17], is specifically induced by Leishmania infection and involved in the deactivation of the IFN-c-induced JAK2-dependent signaling pathway [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of bone-marrow macrophages from me/me and wild-type mice have suggested that SHP-1 regulates interferon-␣-induced Jak-Stat signaling (30) as well as CSF-1-induced tyrosine phosphorylation and cell proliferation (31), and associates constitutively with an unidentified 130-kDa phosphotyrosyl protein (pp130) (31). Subsequently, pp130 was shown to be a membrane-spanning glycoprotein and a substrate of SHP-1 in macrophages and was identified as comprising p91/PIR-B (32,33), a recently cloned ITIM-containing inhibitory receptor (34,35) and SHPS-1 (36), or the SHPS-1-related protein BIT (32).…”
Section: Occurred Independently Of P62mentioning
confidence: 99%